Identification of a splice variant of mouse TRPA1 that regulates TRPA1 activity - Zhou, Yiming (Nat Commun, 2013)
Transient receptor potential ankyrin 1 (TRPA1) protein is a nonselective cation channel. Although many studies suggest that TRPA1 is involved in inflammatory and neuropathic pain, its mechanism remains unclear. Here we identify an alternative splice variant of the mouse Trpa1 gene. TRPA1a (full-length) and TRPA1b (splice variant) physically interact with each other and TRPA1b increases the expression of TRPA1a in the plasma membrane. TRPA1a and TRPA1b co-expression significantly increases current density in response to different agonists without affecting their single-channel conductance. Exogenous overexpression of Trpa1b gene in wild-type and TRPA1KO DRG neurons also increases TRPA1a-mediated AITC responses. Moreover, expression levels of Trpa1a and Trpa1b mRNAs change dynamically in two pain models (complete Freund’s adjuvant-induced inflammatory pain and partial sciatic nerve ligation-induced neuropathic pain models). These results suggest that TRPA1 may be regulated through alternative splicing under these pathological conditions.